Kaizen implementation: A lean strategy to improve healthcare performance - Sanches Zeferino, Ana Carolina; de Souza Ramos, José Ricardo; Santos, Alexandre Beraldi; Satolo, Eduardo Guilherme [UNESP]; Neto, Olavo Braga; Bourguignon, Saulo Cabral (IGI Global, 2022)
The use of the lean philosophy in healthcare environments has been reported in different countries, both in the private and the public sectors. However, there is not much information on how to apply the Kaizen concept to healthcare services, notably in hospitals and emergency services, which are increasingly challenging environments given the aging of the world population and the degradation of human conditions in several countries. Existing publications on the topic expose different forms of Kaizen use in healthcare services, which may cause misunderstanding and confusion. This chapter describes and brings light to the Kaizen approach in lean implementations and discusses its challenges, barriers, and success factors using a case study of a non-governmental organization (NGO) that started its lean journey with Kaizen implementation in late 2019. It also describes strategies to use it according to up-to-date publications and presents the benefits, the challenges, and the framework to successfully implement Kaizen.